The Unbanked - Johnston, Don Jr.; Morduch, Jonathan (World Bank, 2012)
To analyze the prospects for expanding financial access to the poor, bank professionals assessed 1,438 households in six provinces in Indonesia to judge their creditworthiness. About 40 percent of poor households were judged creditworthy according to the criteria of Indonesia's largest microfinance bank, but fewer than 10 percent had recently borrowed from a microbank or formal lender. Possessing collateral appeared as a minor determinant of creditworthiness, in keeping with microfinance innovations. Although these households were judged able to service loans reliably, most desired small loans. Calculations show that the bank, given its current fee structure and banking practices, would lose money when lending at the scales desired. So, while innovations have helped to extend financial access, it remains difficult to lend in small amounts and cover costs.